Assessment of anticancer, antimicrobial, antidiabetic, anti-obesity and antioxidant activity of Ocimum Basilicum seeds essential oil from Palestine - Ahmad M Eid; Nidal Jaradat; Naser Shraim; Mohammed Hawash; Linda Issa; Mohammad Shakhsher; Nour Nawahda; Ali Hanbali; Noor Barahmeh; Basil Taha; Ahmed Mousa (BMC, 2023)
Abstract Background Many modern pharmaceutical researchers continue to focus on the discovery and evaluation of natural compounds for possible therapies for obesity, diabetes, infections, cancer, and oxidative stress. Extraction of Ocimum basilicum seed essential oil and evaluation of its antioxidant, anti-obesity, antidiabetic, antibacterial, and cytotoxic activities were the goals of the current study. Method O. basilicum seed essential oil was extracted and evaluated for its anticancer, antimicrobial, antioxidant, anti-obesity, and anti-diabetic properties utilizing standard biomedical assays. Results O. basilicum seed essential oil showed good anticancer activity against Hep3B (IC50 56.23 ± 1.32 µg/ml) and MCF-7 (80.35 ± 1.17 µg/ml) when compared with the positive control, Doxorubicin. In addition, the essential oil showed potent antibacterial (against Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Proteus mirabilis, and Pseudomonas aeruginosa) and antifungal (against Candida albicans) activities. Moreover, as for the anti-amylase test, IC50 was 74.13 ± 1.1 µg/ml, a potent effect compared with the IC50 of acarbose, which was 28.10 ± 0.7 µg/ml. On the other hand, for the anti-lipase test, the IC50 was 112.20 ± 0.7 µg/ml a moderate effect compared with the IC50 of orlistat, which was 12.30 ± 0.8 µg/ml. Finally, the oil had a potent antioxidant effect with an IC50 of 23.44 ± 0.9 µg/ml compared with trolox (IC50 was 2.7 ± 0.5 µg/ml). Conclusion This study has provided initial data that supports the importance of O. basilcum essential oil in traditional medicine. The extracted oil not only exhibited significant anticancer, antimicrobial, and antioxidant properties but also antidiabetic and anti-obesity effects, which provided a foundation for future research.